Study of Instability Mechanism and Roof Caving Mode of Cementing Filling Stope: The Case Study of a Nonferrous Metal Mine in China - Zhong, Min; Yang, Peng; Hu, Ying-Peng (Advances in Civil Engineering, 2022)
The downward layered cemented filling method, which is generally used in the mining of high-value metal mines with poor surrounding rock quality, is widely believed to not cause large-scale instability of the roof strata in the mining area. However, a nonferrous metal mine in northern China, which has been using the downward cemented filling method, suddenly suffered a violent collapse accident of the stope roof, and the surface is accompanied by significant subsidence on a large scale. The accident revealed that the roof collapse mechanism still needed further research. In this paper, field investigation and numerical simulation were combined to study the mechanism of roof collapse. Based on the input data including in-situ stress state, geological occurrence pattern, and mining steps, the particle flow code (PFC) was used to simulate the stress and displacement changes of the rock mass under mining disturbance. These results indicate that the failure process of the overlying rock mass can be divided into four stages due to the special geological conditions of the mine: pillar stability stage, pillar chain failure stage, roof filling caving stage, and gneiss plug settlement stage. In the early stage of mining, the pillars between the mined-out drifts could effectively support the overlying rock mass due to the small exposed roof. As more drifts were mined, the vertical pressure on the pillars was added. When the number of mining drifts reached five, one of the pillars was firstly destroyed due to overloading, and then the pressure of the overlying strata was transferred to the surrounding pillars, leading to the subsequent failure of other pillars. When pillars were damaged, arch caving appeared inside the roof filling material. Finally, the vertical shear resistance capacity of the gneiss mass above is insufficient, owing to the steeply dipping joints. Finally, the gneiss above was subject to sudden plug settlement along the vertical joints. It should be noted that the stope mining management of the mine has a significant impact on production safety. In order to ensure the stability of the stope formed by cemented filling method, the dense distribution of simultaneous mining drifts should be avoided and the mine-out areas should be backfilled in time.